Deformation incompatibility enables hetero-deformation induced strengthening in Ti/Nb laminates. Issue 2 (1st February 2023) - Jiang, S.; Lin Peng, R.; Zhao, X.; Zuo, L.; Jia, N.
ABSTRACT: Deformation incompatibility in Ti/Nb laminates under uniaxial tension was revealed by in-situ neutron diffraction. During uniform deformation of the bulk laminates, the hard Nb constrained by the soft Ti showed moderate work hardening and only slightly decreased flow stress. The mechanical incompatibility accumulated in both elastic and elasto-plastic regimes between the metals lead to pronounced hetero-deformation induced (HDI) strengthening, and the HDI stress was comparable to the maximum phase-to-phase interaction. The HDI hardening and interphase stress showed consistent evolution trends, implying that the interaction between dissimilar metals can be used as an important indicator for evaluating HDI strengthening and hardening. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The phase-to-phase interaction is found to be an important indicator for evaluating the HDI strengthening and hardening in heterogeneous laminates, and the microstress analysis can guide the design of heterostructures.